The effects of calmodulin kinase II inhibitor on ventricular arrhythmias in rabbits with cardiac hypertrophy - Ke, Jun; Zhang, Cun-tai; Ma, Ye-xin; Liu, Jun; Zhang, Qing-yang; Liu, Nian; Ruan, Yan-fei; Lin, Li (Zhōnghuá xīnxuèguănbìng zázhì, 2007)
To investigate the effect of KN-93, a calmodulin kinase II inhibitor, on ventricular arrhythmias in rabbits with cardiac hypertrophy. Female New Zealand white rabbits were randomly divided into four groups (n = 10 each): Sham; LVH; LVH + KN-92 and LVH + KN-93 group. LVH was induced by partially constricting the abdominal aorta. In Sham group, the abdominal aorta was exposed without constriction. Eight weeks later, the arterially perfused left ventricular wedge preparations were made and transmembrane action potentials (TAP) from epicardium and endocardium and transmural ECG were simultaneously recorded. Incidence of early after depolarization (EAD) and torsade de pointes (Tdp), QT interval, action potential duration (APD) and transmural depolarization dispersion (TDR) at different cycle lengths were observed under slow stimulation (2000 - 4000 ms), hypokalemic (2 mmol/L) and hypomagnesaemic (0.25 mmol/L) Tyrode's solution perfusion. Left ventricular hypertrophy was detected in LVH group by echocardiography an